Система библиотечно-информационного обеспечения специалистов по архитектуре и строительству - Гаджиева, Г.; Гаджиєва, Г.; Hajiyeva, G. (My University, 2016)
Статья посвящена формированию библиотечно-информационной системы обеспечения таких направлений архитектуры, как исследование национально-архитектурных школ в истории Азербайджана и деятельности современных архитектурных школ, научные разработки молодых архитекторов и т. д. Исследование может стать подспорьем для научных разработок молодых архитекторов в изучении научно-культурных и образовательных сфер своей науки, для определения роли информационно-библиотечных ресурсов в своей работе.

Стаття присвячена формуванню бібліотечно-інформаційної системи забезпечення таких напрямів архітектури, як дослідження національно-архітектурних шкіл в історії Азербайджану та діяльності сучасних архітектурних шкіл, наукові розроблення молодих архітекторів тощо. Дослідження може стати підмогою для наукових доробків молодих архітекторів у вивченні науково-культурних і освітніх сфер науки, визначення ролі інформаційно-бібліотечних ресурсів у своїй роботі.

Azerbaijani culture having deep and diverse historical roots is a complex part of the world culture. Domestic researchers play an important role in the study of the roots of culture. Their works favorably vary from those where anti-scientific concepts are put forward, the architectural heritage of Azerbaijan is reflected incorrectly, denying the uniqueness of cultures of individual nations and describing them outside of time and space frames. In recent years, Azerbaijan carried out some research work in the consideration of the information society in library science, knowledge systems that make up its foundation, as well as library and information system providing specific scientific areas. We would like to note that the study of library and information provision systems in a variety of scientific fields, including architecture, is a new direction in the activity of the scientific community. This article is devoted to formation of library and information provision system of such architectural areas as the study of the national schools of architecture in the history of Azerbaijan, the activity of the modern schools of architecture, research and development of young architects, etc. The research can be helpful to the scientific development of young architects in the study of scientific and cultural and educational spheres of the science, the definition of the role of information and library resources in their work.
Гаджиева Г. Система библиотечно-информационного обеспечения специалистов по архитектуре и строительству / Г. Гаджиева // Актуальні проблеми філософії та соціології: Науково-практичний журнал / Голов. ред. Д. В. Яковлев; відпов. секретар І. В. Шамша; Міністерство освіти і науки України; Національний університет "Одеська юридична академія". - Одеса, 2016. - Вип. 13. - С. 14-16.
Keywords: архитектурная деятельность; архитектор; специалист; библиотека; библиографические ресурсы; документально-информационное обеспечение; архітектурна діяльність; архітектор; фахівець; бібліотека; бібліографічні ресурси; документально- інформаційне забезпечення; architectural activity; architect; specialist; library; bibliographic resources; documentary and information provision